HALO LBH : APLIKASI KONSULTASI HUKUM BERBASIS ANDROID DENGAN FRAMEWORK REACT NATIVE - Leandra Chika Gayatri (2021)
Indonesia is a legal state where all activities of the Indonesian people, both real and virtual, have been protected by applicable laws. However, there is a lack of public awareness and understanding of the law. This causes people not to know what steps can be taken, and where they can get protection for their rights when they are involved in legal problems. So we need a legal service in the form of consultation as the first step for the community in finding solutions to problems related to the law so that the community can take steps in accordance with applicable laws effectively and efficiently. This study aims to create an application that can facilitate the community in obtaining legal aid services using the Waterfall System Development Life Cycle (SDLC) method. The implementation of the Waterfall SDLC method is carried out starting with Analysis and Definition of Requirements by conducting questionnaires and interviews, followed by system design by making UML (Unified Modeling Language) diagrams, then implementing the system using the Android-based React Native Framework, and testing the system using the black-box testing method. In this study resulted in a legal consultation application based on Android with seven main processes and features, namely live chat that functions well.